Metagenomic characterization of the tracheobronchial microbiome in lung cancer - Bailey, Alexis; Hogue, Stephanie; Pierce, Christine M.; Paul, Shirlene; La Fuente, Natalie; Thapa, Ram; Kim, Youngchul; Robinson, Lary A. (Frontiers in Microbiomes, 2024)
BackgroundThe tracheobronchial and oral microbiome may be associated with lung cancer, potentially acting as predictive biomarkers. Therefore, we studied the lung and oral bacteriome and virome in non-small cell lung cancer (NSCLC) patients compared to melanoma controls to discover distinguishable features that may suggest lung cancer microbial biomarkers.MethodsIn this pilot case-control study, we recruited ten patients with early-stage NSCLC (cases) and ten age-matched melanoma patients (controls) who both underwent tumor resection. Preoperative oral gargles were collected from both groups, who then underwent transbronchoscopic tracheal lavage after intubation. Lung tumor and adjacent non-neoplastic lung were sterilely collected after resection. Microbial DNA from all lung specimens underwent 16S rRNA gene sequencing. Lavage and gargle specimens underwent whole-genome shotgun sequencing. Microbiome metrics were calculated to compare both cohorts. T-tests and Wilcoxon rank sum tests were used to test for significant differences in alpha diversity between cohorts. PERMANOVA was used to compare beta diversity.ResultsNo clear differences were found in the microbial community structure of case and control gargles, but beta diversity of case and control lavages significantly differed. Two species, Granulicatella adiacens and Neisseria subflava, which are both common oral commensal organisms, appeared in much higher abundance in case versus control lavages. Case lavages also maintained higher relative abundances of other oral commensals compared to controls.ConclusionsLung lavages demonstrated oral microbiota enrichment in cases compared to controls, suggesting microaspiration and resultant inflammation. The oral commensals Granulicatella adiacens and Neisseria subflava were more abundant in the tracheobronchial lavages of lung cancer versus melanoma patients, implicating these microorganisms as potential lung cancer biomarkers, warranting further validation studies.